Consumption Practices: A Virtue Ethics Approach - Garcia-Ruiz, Pablo (Business ethics quarterly, 2014)
Ethical research on consumption has focused mainly on the obligations, principles and values guiding consumers' actions and reasons for action. In doing so, it has concerned itself mostly with such bounded contexts as voluntary simplifiers, anti-consumption movements or so-called ‘ethical consumers,’ thereby fostering an artificial opposition between ethical and non-ethical consumption. This paper proposes virtue ethics as a more apt conceptual framework for the ethical analysis of consumption because it takes into account the developmental dynamic triggered by engagement in consumption practices. We build on MacIntyre's goods-virtues-practices-institutions framework and Beabout's concept of a domain-relative practice and argue that when engaging in consumption activities, agents may pursue goods internal to practices, further their individual life narratives and contribute to the good of their communities, thus developing virtues that perfect themselves both as consumers and as ethical agents.